The Effect of IT Investment and Carbon Emission Disclosure on Firm Value A Case Study of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2020-2024 - Ersita Sisilia; Muhammad Anggionaldi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research looks at how investments in information technology and the disclosure of carbon emissions impact the value of manufacturing companies that are listed on the Indonesia Stock Exchange (IDX), specifically during the years 2020 through 2024. This study uses a quantitative method with secondary data obtained from annual reports and sustainability reports. The sampling technique used is purposive sampling, resulting in 10 companies with a total of 50 observations, and hypothesis testing was performed using t-tests and F-tests as the basis for examining the partial and simultaneous effects of the variables. The partial results of the study show that IT Investment and Carbon Emission Disclosure have a negative and significant effect on Company Value. Meanwhile, simultaneous testing shows that IT Investment and Carbon Emission Disclosure have a significant effect on company value. The results of this study imply the importance of companies managing IT investment and emission disclosure strategically so that they are not considered a cost burden. Further research is recommended to add moderating or mediating variables to clarify the conditions that can strengthen firm value.